Edukasi Digital Parenting untuk Meningkatkan Pemahaman dan Kepedulian Orang Tua terhadap Anak di Era Digital - Hadi Wibowo, Teguh; Hidayatullah, Ahmad Syauqi; Subekti, Nanang Bagus; Djufri, Elyas (Santri : Journal of Student Engagement, 2025)
The rapid advancement of digital technology has profoundly influenced family parenting styles, especially in managing the growing threats of digital-age juvenile delinquency, such as online gambling, sexting, and illegal loan practices. Despite this, many parents still face limitations in both knowledge and digital skills, making it difficult to guide and supervise their children's online activities effectively. This community engagement initiative was designed to enhance parental awareness and understanding of digital parenting. Conducted in Bometen Hamlet, Ngandong Village, Gantiwarno Subdistrict, Gunung Kidul Regency, the program applied a Participatory Action Research (PAR) approach. A total of 30 participants—16 parents and 14 adolescents—were actively involved in four stages: observation, planning, implementation, and evaluation. The evaluation outcomes revealed a significant improvement in both awareness and comprehension of digital risks. Adolescents demonstrated a 66% increase in awareness and a 41% improvement in understanding, while parents showed a 33% rise in awareness and a 61% gain in understanding. These findings highlight the effectiveness of participatory educational strategies in building stronger digital parenting capacity and fostering more adaptive and communicative family environments in the face of technological change.